Concept-rich mathematics instruction : building a strong foundation for reasoning and problem solving - Ben-Hur, Meir (Gale virtual reference library., 2006)
Presents an instructional approach that helps students in every grade level understand math concepts so they can apply them on assessments, across the curriculum, and outside of school. Provides teaching practices and lesson ideas that give students a stronger foundation for reasoning and problem solving.